Insulin Resistance and β-Cell Function of Lean versus Overweight or Obese Filipino Patients with Newly Diagnosed Type 2 Diabetes Mellitus - Bautista, Francesca Paula (J ASEAN Fed Endocr Soc, 2019)
OBJECTIVES: To compare the level of insulin resistance and β-cell function between lean and overweight/obese Filipino patients with newly diagnosed type 2 diabetes mellitus (T2DM). METHODOLOGY: This was a cross-sectional analytical study including newly diagnosed T2DM Filipino patients from St. Luke’s Medical Center - Quezon City. The patients were classified as either lean or overweight/obese. Age, sex, smoking history, anthropometric measures and blood pressure were obtained. Insulin resistance and β-cell function were determined using the homeostasis model assessment (HOMA). The original model (HOMA1) and the updated model (HOMA2) were used. RESULTS: A total of 80 subjects were included. There were 40 subjects in each group. The overweight/obese subjects had significantly higher mean insulin resistance (HOMA1-IR 9.8±11.7, HOMA2-IR 3.0±2.0) compared to the lean group (HOMA1-IR 2.9±1.5, HOMA2-IR 1.3±0.5). This was consistent in both HOMA1 and HOMA2 (p-values=0.001 and <0.001, respectively). The mean β-cell function of the overweight/obese patients was significantly higher than the lean subjects when using HOMA1 (lean=57.8±35.5, overweight/obese=93.6±66.4, p-value=0.003), but not in HOMA2 (lean=57.6±30.5, overweight/obese=74.8±45.7, p-value=0.051). Overweight/obesity increased HOMA1-IR by 4.0 and HOMA1-B by 46.1 (p-values= 0.002 and <0.001, respectively). Through the use of HOMA2, overweight/obesity increased HOMA2-IR by 1.4 and HOMA2-B by 29.1 (p-values<0.001). Being overweight/obese was also associated with significantly higher odds for developing greater insulin resistance (HOMA1-IR adjOR = 5.6, 95%CI= 1.7-19.2, p-value=0.005; HOMA2-IR adjOR=10.9, 95%CI=3.4-34.9, p-value<0.001) and lower odds for a decreased β-cell function (HOMA1-B adjOR = 0.2, 95%CI = 0.05-0.9, p-value=0.033; HOMA2-B adjOR=0.2, 95%CI=0.04-0.9, p-value=0.043) compared to being lean. CONCLUSION: Newly diagnosed overweight/obese T2DM had higher mean insulin resistance and β-cell function compared to lean T2DM. Overweight/obesity was also associated with higher odds of developing insulin resistance and lower odds for a decreased β-cell function compared to being lean. The overweight/obese T2DM group also had worse metabolic profile manifested by higher FPG, HbA1c, SGPT and blood pressures compared to the lean T2DM group.